Sergei Gerasimov's The Young Guard: artistic method and the conflict of discourses of history and power. (4th May 2019) - Kazyuchits, Maksim
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK this article is devoted to the history of the creation of the film The Young Guard (1948) by the famed Soviet director Sergei Gerasimov. The director was able to turn the work on the film into a grand artistic experiment. He managed to synthesize the educational process (his own acting-directing course at the Film Institute VGIK), the theatrical tradition (performances in the Theatre of Film Actors), and film production (in the film studio Soyuzdetfilm). Particular attention is paid to an analysis of the phenomenon of The Young Guard, its rapid transformation from the historical fact of the national tragedy of World War II to the artistic image in Aleksandr Fadeev's novel and Gerasimov's film, and then to the sociopolitical myth that answers the request for a discourse on power.